The Relationship between Gifted Students’ Scientific Epistemological Beliefs and Climate Change Awareness Levels - Yesim Ozdeniz; Hilal Aktamis (Journal of Education in Science, Environment and Health)
One of the most talked about and discussed topics in our current time is climate change. Therefore, it is important to draw attention to this issue in educational environments. The purpose of this study is to examine the relationship between scientific epistemological beliefs and climate change awareness of gifted students and whether these variables differ according to gender. The study was conducted using a relational screening model. The Scientific Epistemological Belief Scale and the Global Warming/Climate Change Awareness Scale were used as data collection tools. The sample of the study consists of 106 gifted students at the secondary school level in a city in the western region of Turkey. The research findings showed that there was a relationship between the epistemological beliefs of gifted students and their awareness levels of the causes and effects of climate change, their awareness of personal initiatives, and their tendency to change behaviour. In addition, the awareness level of personal initiatives to prevent climate change and the scientific epistemological belief levels differed significantly in favor of gifted female students.